The first three elements of the hermeneutic situation in Martin Heidegger - Stefan VLADUTESCU; Victor Justice PITSOE (Social Sciences and Education Research Review)
The present study opens an analysis of the fundamental elements of the hermeneutic situation in Martin Heidegger. The prerequisites, the partners and the hermeneutic relationship are evaluated as cardinal aspects of the hermeneutic situation. The prerequisites represent the initial consciousness of the presuppositions that establish the relationship between the partners. There are three prerequisites